Modeling the acceptability of BCIs for motor rehabilitation after stroke: A large scale study on the general public - Grevet, Elise; Forge, Killyam; Tadiello, Sebastien; Izac, Margaux; Amadieu, Franck; Brunel, Lionel; Pillette, Léa; Py, Jacques; Gasq, David; Jeunet-Kelway, Camille (Frontiers in Neuroergonomics, 2023)
Strokes leave around 40% of survivors dependent in their activities of daily living, notably due to severe motor disabilities. Brain-computer interfaces (BCIs) have been shown to be efficient for improving motor recovery after stroke, but this efficiency is still far from the level required to achieve the clinical breakthrough expected by both clinicians and patients. While technical levers of improvement have been identified (e.g. sensors and signal processing), fully optimised BCIs are pointless if patients and clinicians cannot or do not want to use them. We hypothesise that improving BCI acceptability will reduce patients’ anxiety levels, while increasing their motivation and engagement in the procedure, thereby favouring learning and, ultimately, motor recovery. In other terms, acceptability could be used as a lever to improve BCI efficiency. Yet, studies on BCI acceptability are missing in the literature. Thus, our goal was to model this acceptability in the context of post-stroke motor rehabilitation, and to identify its determinants. The main outcomes of this paper are the following: i) we designed the first model of acceptability of BCIs for motor rehabilitation after stroke, ii) we created a questionnaire to assess acceptability based on that model and distributed it on a sample representative of the general public in France (N=753, this high response rate strengthens the reliability of our results), iii) we validated the structure of this model and iv) quantified the impact of the different factors on this population. Results show that BCIs are associated with high levels of acceptability in the context of motor rehabilitation after stroke and that the intention to use them in that context is mainly driven by the perceived usefulness of the system. In addition, providing people with clear information regarding BCI functioning and scientific relevance had a positive influence on acceptability factors and behavioural intention. With this paper we propose a basis (model) and a methodology that could be adapted in the future in order to study and compare the results obtained with: i) different stakeholders, i.e., patients and caregivers; ii) different populations of different cultures; and iii) different targets, i.e., other clinical and non-clinical BCI applications.